An overview: metal-based inhibitors of urease. (31st December 2023) - Yang, Wei; Peng, Zhiyun; Wang, Guangcheng
Abstract: Urease is a kind of nickel-dependent metalloenzyme, which exists in the biological world widely, and can catalyse the hydrolysis of urea into ammonia and carbon dioxide to provide a nitrogen source for organisms. Urease has important uses in agriculture and medicine because it can catalyse the production of ammonia. Therefore, in this review, metal-based inhibitors of urease will be summarised according to different transition metal ions. Including the urease inhibition, structure–activity relationship, and molecular docking. Importantly, among these reviewed effective urease inhibitors, most of copper metal complexes exhibited stronger urease inhibition with IC50 values ranging from 0.46 μM to 41.1 μM. Significantly, the collected comprehensive information looks forward to providing rational guidance and effective strategies for the development of novel, potent, and safe metal-based urease inhibitors, which are better for practical applications in the future.